Outcome of Buccal Mucosal Graft Urethroplasty in Long Segment Anterior Urethral Stricture (Bangladesh Journal of Urology, 2020)
Objective: To assess the success of BMG urethroplasty in long segment anterior urethral stricture.Method: From January 2014 to December 2015, twenty male patients with long anterior segment urethral stricture were managed by BMG urethroplasty. After voiding trial they were followed up at 3 month with Uroflowmetry, RGU & MCU and PVR measurement by USG. Patients were further followed up with Uroflowmetry and PVR at 6 months interval.Successful outcome was defined as normal voiding with a maximum flow rate >15ml /sec and PVR